Hydrogen storage alloy composite material and preparation and application thereof
A hydrogen storage alloy composite material is prepared by mechanically mixing and calcining carbon-coated nickel and/or carbon-coated cobalt materials with hydrogen storage alloys, which solves the problems of easy oxidation of hydrogen storage alloys and decreased hydrogen storage rate, and achieves efficient anti-oxidation and kinetic properties.
Patent Information
- Application Number
- CN202410455785.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-10-24
AI Technical Summary
When existing carbon materials are coated on hydrogen storage alloy materials, the hydrogen storage rate and the maximum hydrogen storage capacity are reduced. At the same time, the hydrogen storage alloy is easily oxidized in the air and has insufficient antioxidant capacity.
A hydrogen storage alloy composite material is prepared by mechanically mixing carbon-coated nickel material and/or carbon-coated cobalt material with a hydrogen storage alloy material and calcining the mixture. The carbon material is evenly dispersed on the alloy surface, preventing air oxidation without affecting hydrogen diffusion.
The air oxidation resistance of hydrogen storage alloys is improved, good hydrogen storage kinetics are maintained, volume changes during hydrogen absorption and desorption are alleviated, and hydrogen desorption performance is improved.
Smart Images

Figure CN120829142A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of hydrogen storage material preparation, in particular to a hydrogen storage alloy composite material and its preparation and application. BACKGROUND
[0002] Hydrogen energy is an ideal renewable energy carrier, and hydrogen storage is the key to the development and application of hydrogen energy technology. Many countries have listed hydrogen storage technology as a key technology for future scientific and technological development. Hydrogen storage alloy can store and release hydrogen at room temperature, and the hydrogen released after hydrogen storage has high purity. Based on the characteristics of the material, it can purify industrial gray hydrogen. In summary, hydrogen storage alloy is considered an ideal hydrogen storage material. However, hydrogen storage alloy is easily oxidized in air, so improving the oxidation resistance of hydrogen storage alloy has been a research hotspot for many years.
[0003] Hydrogen storage alloy has the problem of being easily oxidized in air. In recent years, some researchers have modified the outer surface of hydrogen storage alloy to improve the oxidation resistance of the material. Niu et al. (Chemical Physics Letters, 2021, 778: 138762.) coated Co2B alloy composite material with mesoporous carbon CMK-3 for electrochemical hydrogen storage, and found that the discharge capacity reached a maximum value (662.8 mAh / g) when the doping amount of CMK-3 was 5%. The CMK-3 / Co2B composite material showed good corrosion resistance and oxidation resistance. CMK-3 / Co2B has unique electrocatalytic activity and structural characteristics of CMK-3, so it has excellent electrochemical and kinetic properties, which can accelerate the transmission of hydrogen. Zhang et al. (Materials Letters, 2022, 329(15): 133249.) constructed carbon-coated La-Mg intermetallic compound nanocrystals to improve the hydrogen storage stability. After ten cycles, the hydrogen desorption capacity of the carbon-coated sample was 3.5 wt.%, which was four times that of the original sample. The coated sample has high hydrogen storage capacity, low dehydrogenation temperature and activity.
[0004] As can be seen from the above, although some researchers have used carbon materials to physically load and functionally modify hydrogen storage alloy materials, the existing method coats carbon materials on the surface of hydrogen storage alloy, which significantly reduces the hydrogen storage rate of hydrogen storage alloy and also reduces the maximum hydrogen storage capacity of the material. SUMMARY
[0005] The purpose of the present application is to overcome the problems existing in the prior art, and to provide a hydrogen storage alloy composite material and its preparation and application. The hydrogen storage alloy composite material provided by the present application has high air oxidation resistance and good hydrogen storage kinetic performance.
[0006] To achieve the above object, the present application provides a hydrogen storage alloy composite material in one aspect, which comprises a hydrogen storage alloy material and a carbon material;
[0007] The carbon material is a carbon-coated nickel material and / or a carbon-coated cobalt material.
[0008] The present application provides a preparation method of the hydrogen storage alloy composite material in a second aspect, which comprises the following steps:
[0009] (1) mechanically mixing the hydrogen storage alloy material and the carbon material to obtain a solid material, wherein the carbon material is a carbon-coated nickel material and / or a carbon-coated cobalt material;
[0010] (2) calcining the solid material obtained in step (1).
[0011] The present application provides an application of the hydrogen storage alloy composite material of the first aspect or the hydrogen storage alloy composite material prepared by the preparation method of the second aspect in hydrogen storage.
[0012] Through the above technical solution, the present application has the following beneficial effects:
[0013] The hydrogen storage alloy composite material provided by the present application has excellent air poisoning resistance through the synergistic effect of the specific type of carbon material (carbon-coated nickel material and / or carbon-coated cobalt material) and the hydrogen storage alloy material. Not only can it block the air from contacting the surface of the covered hydrogen storage alloy material, but also can have good hydrogen storage kinetics performance. At the same time, it can relieve the fine cracks and hydrogen storage alloy material pulverization caused by volume shrinkage during dehydrogenation and volume expansion during hydrogen absorption in the hydrogen absorption and desorption cycle of the hydrogen storage alloy material, reduce the grain boundary migration and grain growth of the hydrogen storage alloy material caused by the heat effect of hydrogen absorption and desorption, and thus improve the hydrogen desorption performance.
[0014] The present application uses a mechanical mixing method to prepare the hydrogen storage alloy composite material, which has a simple process flow and is easy to scale up. Moreover, the preparation method does not introduce water, avoiding the poisoning of the hydrogen storage alloy material. BRIEF DESCRIPTION OF DRAWINGS
[0015] Figure 1 is the XRD pattern of the hydrogen storage alloy composite material of Example 1 and Example 3 and the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 0h;
[0016] Figure 2 is the SEM-mapping element analysis pattern of the hydrogen storage alloy composite material of Example 1 after exposure for 0h;
[0017] Figure 3XRD pattern of the hydrogen storage alloy composite of Example 1, Example 3 and the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 168 h;
[0018] Figure 4 SEM-mapping elemental analysis of the hydrogen storage alloy composite of Example 1 after exposure for 168 h;
[0019] Figure 5 SEM-mapping elemental analysis of the hydrogen storage alloy composite of Example 3 after exposure for 0 h;
[0020] Figure 6 SEM-mapping elemental analysis of the hydrogen storage alloy composite of Example 3 after exposure for 168 h;
[0021] Figure 7 XRD pattern of the hydrogen storage alloy composite of Example 1, Comparative Example 1 and the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 0 h;
[0022] Figure 8 SEM-mapping elemental analysis of the hydrogen storage alloy composite of Comparative Example 1 after exposure for 0 h;
[0023] Figure 9 XRD pattern of the hydrogen storage alloy composite of Example 1, Comparative Example 1 and the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 168 h;
[0024] Figure 10 SEM-mapping elemental analysis of the hydrogen storage alloy composite of Comparative Example 1 after exposure for 168 h;
[0025] Figure 11 SEM-mapping elemental analysis of the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 0 h;
[0026] Figure 12 SEM-mapping elemental analysis of the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 168 h. DETAILED DESCRIPTION
[0027] The endpoints of the ranges and any values disclosed herein are not limited to the precise values stated. The endpoints of the ranges and any values are provided as approximate descriptions of the ranges and are understood to be open-ended. Each range disclosed herein is to be understood to include individual values, and sub-ranges, falling within the stated range. In other words, any numerical range disclosed herein is intended to include all sub-ranges falling within the broader range, and every numerical value within the broader range. In particular, from the broader range 1 to 100%, a preferred sub-range is 40 to 60%, and specific numerical values are 45, 50, 55, and 60%. The disclosure as set forth herein can be, and is intended to be, controlling with respect to the two ends of the ranges but not the individual values falling within the ranges unless the context indicates otherwise.
[0028] The hydrogen storage alloy composite material comprises a hydrogen storage alloy material and a carbon material;
[0029] The carbon material is a carbon-coated nickel material and / or a carbon-coated cobalt material.
[0030] The carbon-coated nickel material / carbon-coated cobalt material and the hydrogen storage alloy material synergize to make the hydrogen storage alloy composite material have good air resistance, which not only blocks air from contacting the surface of the covered hydrogen storage alloy material, but also does not affect the diffusion of hydrogen to the surface of the hydrogen storage alloy material and into the alloy; and the hydrogen storage alloy composite material also has good hydrogen storage kinetics.
[0031] According to the present application, preferably, the mass content of the carbon material in the hydrogen storage alloy composite material is 0.1-10%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, and a range value formed by any two of these point values, preferably 3.5-7%. The preferred embodiment is advantageous in improving the air oxidation resistance of the hydrogen storage alloy composite material and better protecting the hydrogen storage alloy material from air oxidation.
[0032] The content of the carbon material in the hydrogen storage alloy composite material is calculated by the amount of the carbon material.
[0033] According to the present application, preferably, the average particle size of the hydrogen storage alloy composite material is 10-350 μm, preferably 10-30 μm. The preferred embodiment is advantageous in exposing more active sites to the hydrogen storage alloy composite material and improving the probability of contact with hydrogen.
[0034] The average particle size of the hydrogen storage alloy composite material is measured by the laser particle size refraction method.
[0035] According to the present application, preferably, the specific surface area of the carbon material is 200-400 m 2 / g, preferably 200-300 m 2 / g.
[0036] Preferably, the proportion of the mesopore volume in the total pore volume in the carbon material is not less than 90%, preferably not less than 95%.
[0037] In the present application, the specific surface area and pore distribution parameters of the carbon material are measured by the nitrogen adsorption / desorption method.
[0038] The carbon material with the above characteristics is beneficial to hydrogen adsorption through the carbon layer coated on the surface of the hydrogen storage alloy phase, and contact with the hydrogen storage alloy phase for the hydrogen storage process. Compared with the original carbon coated material, hydrogen is more easily entered, accelerating the hydrogen storage rate of the hydrogen storage alloy and improving the maximum hydrogen storage capacity of the material per unit time.
[0039] According to the present application, preferably, in the carbon-coated nickel material, the mass ratio of carbon element to nickel element is 1-4:6-9, for example, it can be 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6 and a range value composed of any two of these point values. With this preferred embodiment, it is beneficial to improve the air oxidation resistance of the hydrogen storage alloy composite material, while still maintaining good hydrogen storage kinetics. When the mass ratio of carbon to nickel is lower than the range, the prepared composite material has weak oxidation resistance, causing the composite material to be easily poisoned by air and the hydrogen storage performance to decrease; when the mass ratio of carbon to nickel is higher than the range, the carbon content may be too high, hydrogen is not easy to pass through the carbon coating layer to contact the hydrogen storage alloy, and at the same time, the nickel content may be too low, further affecting the slow hydrogen storage rate of the composite material, and the hydrogen storage performance decreases significantly.
[0040] According to the present application, preferably, in the carbon-coated nickel material, the mass ratio of carbon element to nickel element is 1-4:6-9, for example, it can be 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6 and a range value composed of any two of these point values. With this preferred embodiment, it is beneficial to improve the air oxidation resistance of the hydrogen storage alloy composite material, while still maintaining good hydrogen storage kinetics.
[0041] The mass ratio of carbon to nickel in the carbon-coated nickel material and the mass ratio of carbon to cobalt in the carbon-coated cobalt material are obtained by XRF method.
[0042] The source of the carbon-coated nickel material and the carbon-coated cobalt material is not particularly limited in the present application and can be obtained by commercial purchase or self-preparation by conventional methods in the art, as long as the above characteristics are met.
[0043] The type of the hydrogen storage alloy material is widely selected in the present application and can be a conventional selection in the art. Preferably, the hydrogen storage alloy material is selected from at least one of titanium-based hydrogen storage alloy material, rare earth-based hydrogen storage alloy material, vanadium-based hydrogen storage alloy material and magnesium-based hydrogen storage alloy material, and is preferably titanium-based hydrogen storage alloy material. The titanium-based hydrogen storage alloy material has fast hydrogen absorption and desorption speed and wide adjustable range of hydrogen absorption and desorption plateau pressure, and is a better hydrogen storage alloy material.
[0044] The titanium-based hydrogen storage alloy material is preferably selected from at least one of TiMn-based, TiFe-based and TiCr-based hydrogen storage alloy materials, and is preferably a TiMn-based hydrogen storage alloy material. In this preferred embodiment, the hydrogen storage alloy is more easily activated, has moderate hydrogen absorption and desorption reaction plateau pressure, and has a faster hydrogen storage rate.
[0045] The specific type of the TiMn-based, TiFe-based and TiCr-based hydrogen storage alloy material is not particularly limited, and can be a conventional selection in the art, which is not described in detail herein.
[0046] The preparation method of the hydrogen storage alloy composite material is not particularly limited, as long as the hydrogen storage alloy composite material with the above composition and characteristics can be prepared. In order to further improve the performance of the hydrogen storage alloy composite material, the application further provides a preparation method of the hydrogen storage alloy composite material.
[0047] The second aspect of the application provides a preparation method of a hydrogen storage alloy composite material, which comprises the following steps:
[0048] (1) mechanically mixing a hydrogen storage alloy material and a carbon material to obtain a solid material, wherein the carbon material is a carbon-coated nickel material and / or a carbon-coated cobalt material;
[0049] (2) calcining the solid material obtained in step (1).
[0050] The hydrogen storage alloy composite material is prepared by the mechanical mixing method, so that the carbon material is uniformly dispersed on the surface of the hydrogen storage alloy material, which is beneficial to improve the air oxidation resistance of the prepared hydrogen storage alloy composite material. At the same time, the method is simple, safe and controllable, and easy to scale up.
[0051] According to the application, preferably, the amount of the hydrogen storage alloy material and the carbon material is such that the mass content of the carbon material in the prepared hydrogen storage alloy composite material is 0.1-10%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, and a range value formed by any two of these point values, and preferably 3.5-7%.
[0052] According to the application, preferably, the specific surface area of the carbon material is 200-400m 2 / g, and preferably 200-300m 2 / g.
[0053] According to the present application, preferably, the mesopore volume accounts for not less than 90% of the total pore volume, more preferably not less than 95%.
[0054] According to the present application, preferably, the mass ratio of carbon element to nickel element in the carbon-coated nickel material is 1-4:6-9, for example, 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, or a range value formed by any two of these point values.
[0055] According to the present application, preferably, the mass ratio of carbon element to cobalt element in the carbon-coated cobalt material is 1-4:6-9, for example, 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, or a range value formed by any two of these point values.
[0056] The present application does not have a particular limitation on the mechanical mixing method of step (1), and a conventional technical means in the art can be used. Preferably, the mechanical mixing of step (1) is performed by a ball milling method. For safety consideration, the mechanical mixing of step (1) is preferably performed by a wet milling method.
[0057] The present application does not have a particular limitation on the specific conditions of the ball milling method, and the conditions can be properly adjusted according to the specific situation, with the average particle size of the hydrogen storage alloy composite material of the first aspect as the criterion. Preferably, the conditions of the ball milling include a rotation speed of 200-500 rpm and a time of 60-360 min.
[0058] According to the present application, preferably, the mechanical mixing process of step (1) includes ball milling mixing of the hydrogen storage alloy material and the carbon material in the presence of an organic solvent.
[0059] The present application has a wide selection range for the type of the organic solvent, and preferably, the organic solvent is an alcohol with 1-3 carbon atoms and / or an alkane with 3-6 carbon atoms, more preferably at least one selected from isopropanol, ethanol, cyclohexane, and ethylene glycol.
[0060] The present application does not have a particular limitation on the amount of the organic solvent, and the amount is determined to ensure the smooth ball milling mixing.
[0061] According to the present application, preferably, the conditions of the calcination of step (2) include a temperature of 200-600 ℃, preferably 400-600 ℃, and a time of 1-6 h. The use of this preferred embodiment is beneficial to obtain a hydrogen storage alloy composite material with graphitized carbon and more beneficial to maintain good hydrogen storage kinetics.
[0062] According to the present application, preferably, the calcination of step (2) is performed in an inert atmosphere.
[0063] The inert atmosphere can be at least one of argon, nitrogen, helium, neon, and the like.
[0064] Preferably, the method further comprises drying the solid product before calcining.
[0065] The drying method is not particularly limited and can be performed by a conventional method in the art, such as vacuum drying.
[0066] According to the present application, preferably, the particle size of the carbon material in step (1) is in the range of 0.01-10 μm, preferably in the range of 0.1-5 μm.
[0067] It can be understood that the particle size of the carbon material is in the range of 0.01-10 μm.
[0068] It should be noted that when the particle size distribution of the carbon material is too large, a longer time and / or a higher speed of ball milling is required to obtain the hydrogen storage alloy composite material of the first aspect of the present application, and in this process, the structural characteristics of the carbon material can be damaged, resulting in a decrease in the air oxidation resistance of the hydrogen storage alloy material.
[0069] According to the present application, preferably, the particle size of the hydrogen storage alloy material in step (1) is in the range of 10-300 μm, preferably in the range of 10-30 μm.
[0070] It can be understood that the particle size of the hydrogen storage alloy material is in the range of 10-300 μm.
[0071] Controlling the particle size distribution of the carbon material and the hydrogen storage alloy material in step (1) in the above range is beneficial to the uniform dispersion of the carbon material on the surface of the hydrogen storage alloy material, and is more beneficial to improving the air oxidation resistance of the hydrogen storage alloy composite material.
[0072] The hydrogen storage alloy material with the particle size distribution can be directly obtained or can be obtained by a conventional technical means in the art (such as ball milling, preferably wet milling).
[0073] According to a specific embodiment of the present application, the hydrogen storage alloy material is subjected to ball milling in the presence of an organic solvent, so that the particle size distribution is in the range of 10-300 μm.
[0074] The hydrogen storage alloy material is not particularly limited and can be a conventional selection in the art. Preferably, the hydrogen storage alloy material is at least one of a titanium-based hydrogen storage alloy material, a rare earth-based hydrogen storage alloy material, a vanadium-based hydrogen storage alloy material, and a magnesium-based hydrogen storage alloy material, and is preferably a titanium-based hydrogen storage alloy material.
[0075] Preferably, the titanium-based hydrogen storage alloy material is selected from at least one of TiMn-based, TiFe-based and TiCr-based hydrogen storage alloy materials, preferably a TiMn-based hydrogen storage alloy material.
[0076] The present application does not have a particular limitation on the specific type of the TiMn-based, TiFe-based and TiCr-based hydrogen storage alloy material, which can be a conventional selection in the art, and will not be described in detail herein.
[0077] The present application provides a use of the hydrogen storage alloy composite material of the first aspect or the hydrogen storage alloy composite material prepared by the preparation method of the second aspect in hydrogen storage.
[0078] The hydrogen storage alloy composite material provided by the present application has high air oxidation resistance, while still maintaining the original reaction rate of the hydrogen storage material, and exhibits excellent hydrogen absorption and desorption performance when applied in hydrogen storage.
[0079] The present application will be described in detail below through examples.
[0080] In the following examples, the hydrogen absorption amount parameter is measured by a HPSA-auto full-automatic high-pressure gas adsorption instrument.
[0081] The titanium-based hydrogen storage alloy material (TM alloy) is a commercially available product of TM5 from Beijing Haoyun Jineng Technology Co., Ltd.
[0082] In the following examples, the carbon-coated nickel material is prepared by adding ethylenediaminetetraacetic acid and nickel hydroxide into deionized water, stirring to obtain a homogeneous solution, and then heating and evaporating to dryness to obtain a solid. The solid is ground and then calcined under a nitrogen atmosphere, and then cooled to room temperature under a nitrogen atmosphere to obtain the carbon-coated nickel material. The composition and material parameters of the carbon-coated nickel material are listed in Table 1.
[0083] Example 1
[0084] The titanium-based hydrogen storage alloy material is first subjected to ball milling treatment in isopropanol solvent to achieve a particle size distribution of 10-25 μm, and then subjected to ball milling treatment with the carbon-coated nickel material (particle size distribution in the range of 0.1-3 μm) in isopropanol solvent under the following ball milling conditions: 400 rpm, 240 min, to obtain a ball-milled material. The ball-milled material is subjected to centrifugal separation to obtain a solid material. The solid material is vacuum dried, and then calcined at 400°C for 4 h in an argon atmosphere to obtain a hydrogen storage alloy composite material. The composition and characteristic parameters of the carbon-coated nickel material are shown in Table 1. The composition and characteristic parameters of the hydrogen storage alloy composite material are shown in Table 1.
[0085] The hydrogen storage alloy composite material prepared above was evenly divided into two batches, one batch was directly subjected to the following characterization test without being exposed to air, and the remaining batch was subjected to the following characterization test after being exposed to air for 168 hours.
[0086] The XRD pattern of the hydrogen storage alloy composite material prepared in Example 1 after exposure for 0 hours is shown as follows: Figure 1 .from Figure 1 It can be seen that the carbon-coated nickel material is well dispersed on the outer surface of the hydrogen storage alloy material.
[0087] The SEM-mapping element analysis diagram of the hydrogen storage alloy composite material prepared in Example 1 after exposure for 0 hours is shown as follows: Figure 2 ( Figure 2 From left to right and from top to bottom, they are SEM image, titanium, nickel, manganese and carbon element overlapping distribution map, titanium element distribution map, manganese element distribution map, carbon element distribution map, nickel element distribution map). Figure 2 It can be seen that the mapping image shows that the carbon and nickel elements in the surface-loaded carbon-coated nickel material are uniformly dispersed on the outer surface of the hydrogen storage alloy material.
[0088] The XRD pattern of the hydrogen storage alloy composite material prepared in Example 1 after exposure for 168 hours is shown as follows: Figure 3 .from Figure 3 It can be seen that after exposure to air for 168 h, the metal diffraction peak signal of the sample decreased and the metal oxide peak increased slightly.
[0089] The SEM-mapping element analysis diagram of the hydrogen storage alloy composite material of Example 1 after exposure for 168 hours is shown as an example. Figure 4 ( Figure 4 From left to right and from top to bottom, they are SEM image, titanium, nickel, manganese, carbon and oxygen element overlapping distribution map, titanium element distribution map, manganese element distribution map, carbon element distribution map, nickel element distribution map, and oxygen element distribution map. Figure 4 It can be seen that the oxygen content on the surface of the hydrogen storage alloy material is small, which indicates that the carbon-coated nickel material plays a certain protective role in isolating the air, preventing the hydrogen storage alloy material from being completely oxidized, and slowing down the oxidation and hydrolysis of the hydrogen storage alloy material.
[0090] Example 2
[0091] The titanium-based hydrogen storage alloy material is first ball-milled in an isopropanol solvent to achieve a particle size distribution of 10-25 μm, and then ball-milled with a carbon-coated nickel material (particle size distribution in the range of 0.1-3 μm) in an isopropanol solvent. The ball milling conditions are: 400 rpm, 120 min, to obtain a ball-milled material. The ball-milled material is centrifuged to obtain a solid material. The solid material is vacuum-dried and then calcined at 400°C in an argon atmosphere for 4 hours to obtain a hydrogen storage alloy composite material. The composition and characteristic parameters of the carbon-coated nickel material are shown in Table 1. The composition and characteristic parameters of the hydrogen storage alloy composite material are shown in Table 1.
[0092] The hydrogen storage alloy composite material prepared above was evenly divided into two batches. One batch was directly subjected to the following characterization test without exposure to air, and the remaining batch was subjected to the following characterization test after exposure to air for 168 hours. The characterization test results were similar to those of Example 1.
[0093] Example 3
[0094] The method of Example 1 was followed, except that the amount of the carbon-coated nickel material was adjusted so that the content of the carbon-coated nickel material in the obtained hydrogen storage alloy composite material was 2.5 wt %.
[0095] The composition and characteristic parameters of the carbon-coated nickel material are shown in Table 1. The composition and characteristic parameters of the hydrogen storage alloy composite material are shown in Table 1.
[0096] Figure 1 The XRD pattern of the hydrogen storage alloy composite material prepared in Example 3 after exposure for 0 hours is shown in FIG. Figure 1 It can be seen that the peak signal of titanium-based hydrogen storage alloy is obvious, while the peak signal of carbon material is too weak and is covered by miscellaneous peaks.
[0097] Figure 5 This is the SEM-mapping element analysis diagram of the hydrogen storage alloy composite material of Example 3 after exposure for 0 hours ( Figure 5 From left to right and from top to bottom, they are SEM image, titanium, nickel, manganese and carbon element overlapping distribution map, titanium element distribution map, manganese element distribution map, carbon element distribution map, nickel element distribution map). Figure 5 It can be seen that the mapping image shows that the carbon and nickel content on the surface of the hydrogen storage alloy material is relatively low, and the surface of the hydrogen storage alloy material cannot be evenly loaded with carbon-coated nickel material.
[0098] Figure 3 This is the XRD pattern of the hydrogen storage alloy composite material after exposure for 168 hours in Example 3. The image shows that the peak of the metal oxide is very obvious.
[0099] Figure 6 This is the SEM-mapping element analysis diagram of the hydrogen storage alloy composite material of Example 3 after exposure for 168 hours ( Figure 6From left to right and from top to bottom, they are SEM image, titanium, nickel, manganese, carbon and oxygen element overlapping distribution map, titanium element distribution map, manganese element distribution map, carbon element distribution map, nickel element distribution map, and oxygen element distribution map. Figure 6 It can be seen that the surface of the hydrogen storage alloy material contains a large amount of oxygen compared to Example 1. This indicates that the carbon-coated nickel material on the outer surface cannot be evenly loaded on the surface of the hydrogen storage alloy material, and therefore cannot play an effective protective role, and the sample is severely oxidized.
[0100] Example 4
[0101] The method of Example 1 was followed, except that a specific surface area of 143.7 m 2 / g, and the proportion of mesopore volume to total pore volume is 70.35% of carbon-coated nickel material (particle size distribution is in the range of 0.1-3μm).
[0102] The composition and characteristic parameters of the carbon-coated nickel material are shown in Table 1. The composition and characteristic parameters of the hydrogen storage alloy composite material are shown in Table 1.
[0103] Comparative Example 1
[0104] The method of Example 1 was followed, except that graphite powder (particle size distribution in the range of 0.01-10 μm, pore size less than 2 nm, purchased from Beijing Bailingwei Technology Co., Ltd., graphite powder 99 wt%) was used instead of carbon-coated nickel material.
[0105] The composition and characteristic parameters of the obtained hydrogen storage alloy composite material are shown in Table 1.
[0106] Figure 7 The XRD pattern of the hydrogen storage alloy composite material of comparative example 1 after exposure for 0 hours. Figure 7 It can be seen that there is an obvious graphite peak in the system.
[0107] Figure 8 This is the SEM-mapping element analysis diagram of the hydrogen storage alloy composite material of comparative example 1 after exposure for 0 hours ( Figure 8 From left to right and from top to bottom in the middle, they are SEM image, local magnification image, titanium, manganese, carbon and oxygen element overlapping distribution image, titanium element distribution image, manganese element distribution image, carbon element distribution image, and oxygen element distribution image. Figure 8 As can be seen, graphite evenly covers the surface of the hydrogen storage alloy, making the resulting hydrogen storage alloy composite material effective in oxidation resistance. However, it hinders hydrogen from entering the interior and reacting with the hydrogen storage alloy, slowing the rate at which hydrogen passes through the surface of the hydrogen storage alloy, resulting in poor hydrogen storage kinetics. However, because graphite slowly absorbs some oxygen at room temperature, a small amount of oxygen is shown in the oxygen distribution diagram.
[0108] Figure 9 is the XRD pattern of the hydrogen storage alloy composite material of Comparative Example 1 after exposure for 168 h. From Figure 9 It can be seen that after the graphite material is loaded on the surface of the hydrogen storage alloy material, the metal oxide impurity peaks are significantly reduced compared with Comparative Example 2.
[0109] Figure 10 is the SEM-mapping elemental analysis pattern of the hydrogen storage alloy composite material of Comparative Example 1 after exposure for 168 h. From left to right and from top to bottom in the figure, the SEM pattern, the titanium-manganese-carbon-oxygen element overlapping distribution pattern, the titanium element distribution pattern, the manganese element distribution pattern, the carbon element distribution pattern, and the oxygen element distribution pattern are sequentially arranged. From Figure 10 It can be seen that the graphite powder is completely distributed on the surface of the titanium-based hydrogen storage alloy, and the oxygen content on the surface of the material is significantly increased due to the continuous absorption of oxygen by the graphite powder. Figure 10
[0110] Comparative Example 2
[0111] The titanium-based hydrogen storage alloy material is first subjected to ball milling treatment in an isopropanol solvent to make the particle size distribution reach 10-25 μm. The material after the ball milling treatment is subjected to centrifugal separation and vacuum drying. The material is used as a hydrogen storage material.
[0112] Figure 1 is the XRD pattern of the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 0 h. From Figure 1 It can be seen that in the titanium-based hydrogen storage alloy, there is no carbon characteristic peak in the curve.
[0113] Figure 11 is the SEM-mapping elemental analysis pattern of the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 0 h. From Figure 11 It can be seen that there is no carbon element and nickel element.
[0114] Figure 3 is the XRD pattern of the titanium-based hydrogen storage alloy material of Comparative Example 2 after exposure for 168 h. From Figure 3 It can be seen that the metal oxide signal peak is very obvious, proving that the hydrogen storage alloy material is fully poisoned by air.
[0115] Figure 12 is the SEM-mapping elemental analysis pattern of the hydrogen storage alloy composite material of Comparative Example 2 after exposure for 168 h. From Figure 12 It can be seen that the surface oxygen element is fully distributed, proving that the material is seriously poisoned by air.
[0116] Table 1
[0117]
[0118] Test Example 1
[0119] For the hydrogen storage alloy composite materials of the examples and the comparative examples exposed in air for 0h and exposed in air for 168h, 1g sample was respectively placed in a HPS-auto full-automatic high-pressure gas adsorption instrument for hydrogen absorption test, and the hydrogen absorption amount within 1h was obtained, and the results are shown in Table 2.
[0120] Table 2
[0121]
[0122] It can be seen from the results in Table 2 that the hydrogen storage alloy composite material prepared by the present application has obviously better hydrogen storage performance, and in combination with the Figures 1-12 It can be seen that the hydrogen storage alloy composite material prepared by the present application has obviously stronger air poisoning resistance, which can effectively improve the problem of weak air poisoning resistance of the existing hydrogen storage alloy material.
[0123] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be considered as disclosed by the present application and belong to the protection scope of the present application.
Claims
1. A hydrogen storage alloy composite material, characterized by comprising a hydrogen storage alloy and a carbon material. The hydrogen storage alloy coated composite material comprises a hydrogen storage alloy material and a carbon material; The carbon material is a carbon-coated nickel material and / or a carbon-coated cobalt material.
2. The hydrogen storage alloy composite material according to claim 1, wherein the mass content of the carbon material in the hydrogen storage alloy composite material is 0.1-10%, preferably 3.5-7%, based on the total weight of the hydrogen storage alloy composite material. Preferably, the average particle size of the hydrogen storage alloy composite material is 10-350 μm, preferably 10-30 μm.
3. The hydrogen storage alloy composite material according to claim 1 or 2, wherein the hydrogen storage alloy material is selected from at least one of a titanium-based hydrogen storage alloy material, a rare earth-based hydrogen storage alloy material, a vanadium-based hydrogen storage alloy material and a magnesium-based hydrogen storage alloy material, preferably a titanium-based hydrogen storage alloy material. Preferably, the carbon material has a mesopore volume accounting for not less than 90%, preferably not less than 95%, of the total pore volume. The specific surface area of the carbon material is 200-400 m 2 / g, preferably 200-300 m 2 / g; Preferably, the mass ratio of carbon element to nickel element in the carbon-coated nickel material is 1-4:6-9. Preferably, the mass ratio of carbon element to cobalt element in the carbon-coated cobalt material is 1-4:6-9.
4. The hydrogen storage alloy composite material according to any one of claims 1-3, wherein the hydrogen storage alloy material is selected from at least one of a titanium-based hydrogen storage alloy material, a rare earth-based hydrogen storage alloy material, a vanadium-based hydrogen storage alloy material and a magnesium-based hydrogen storage alloy material, preferably a titanium-based hydrogen storage alloy material. Preferably, the titanium-based hydrogen storage alloy material is selected from at least one of a TiMn-based, a TiFe-based and a TiCr-based hydrogen storage alloy material, preferably a TiMn-based hydrogen storage alloy material. The preparation method comprises the following steps: (1) mechanically mixing a hydrogen storage alloy material with a carbon material to obtain a solid material, wherein the carbon material is a carbon-coated nickel material and / or a carbon-coated cobalt material; 5. A method for preparing a hydrogen storage alloy composite material, characterized in that: (2) calcining the solid material obtained in step (1).
6. The preparation method according to claim 5, wherein the amount of the hydrogen storage alloy material and the carbon material is such that the mass content of the carbon material in the hydrogen storage alloy composite material obtained is 0.1-10%, preferably 3.5-7%, based on the total weight of the hydrogen storage alloy composite material. Preferably, the carbon material has a mesopore volume accounting for not less than 90%, preferably not less than 95%, of the total pore volume. Preferably, the mass ratio of carbon element to nickel element in the carbon-coated nickel material is 1-4:6-9. Preferably, the mass ratio of carbon element to cobalt element in the carbon-coated cobalt material is 1-4:6-9. Preferably, the specific surface area of the carbon material is 200-400 m 2 / g, preferably 200-300 m 2 / g; 7. The preparation method according to claim 5, wherein the mechanical mixing in step (1) is performed by a ball milling method, preferably a wet ball milling method. Preferably, the ball milling conditions include a rotation speed of 200-500 rpm and a time of 60-360 min. Preferably, the mechanical mixing in step (1) comprises ball milling the hydrogen storage alloy material and the carbon material in the presence of an organic solvent. Preferably, the organic solvent is selected from at least one of isopropyl alcohol, ethanol, cyclohexane and ethylene glycol.
8. The preparation method according to any one of claims 5-7, wherein the calcining in step (2) is performed at a temperature of 200-600°C, preferably 400-600°C, for a time of 1-6 h. Preferably, the calcination in step (2) is carried out under an inert atmosphere.
9. The production method according to any one of claims 5 to 8, wherein, The particle size of the carbon material in step (1) is in the range of 0.01 to 10 μm, preferably in the range of 0.1 to 5 μm; Preferably, the particle size of the hydrogen storage alloy material in step (1) is in the range of 10 to 300 μm, preferably in the range of 10 to 30 μm; Preferably, the hydrogen storage alloy material is selected from at least one of a titanium-based hydrogen storage alloy material, a rare earth-based hydrogen storage alloy material, a vanadium-based hydrogen storage alloy material and a magnesium-based hydrogen storage alloy material, and is preferably a titanium-based hydrogen storage alloy material. Preferably, the titanium-based hydrogen storage alloy material is selected from at least one of a TiMn-based, a TiFe-based and a TiCr-based hydrogen storage alloy material, and is preferably a TiMn-based hydrogen storage alloy material.
10. Use of the hydrogen storage alloy composite material according to any one of claims 1 to 4 or produced by the production method according to any one of claims 5 to 9 in hydrogen storage.